Designing a Citizenship Education Curriculum based on the Concept of Merdeka Belajar Kampus Merdeka (MBKM) in Higher Education - Permana, Ujang; Rahmawati, Aeni (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The Citizenship Education Curriculum is a device unit regarding goals, materials, tactics, and practical evaluation of Citizenship Education as capital in achieving a national education orientation. This study aims to describe the designing of a Citizenship Education Curriculum based on the concept of Merdeka Belajar Kampus Merdeka in Higher Education. This research was carried out through a qualitative approach using the literature study method. The sources of this research are focused on various primary sources and are supported by secondary sources. Data analysis is done by data reduction, data display, verification, or drawing conclusions. Based on this research, independent learning at the independent campus encourages and facilitates students' rights to master various knowledge that is useful for entering the world of work and provides opportunities for students to have other learning experiences outside of their study program. The development of the Citizenship Education curriculum, based on the concept of an independent campus, needs to reflect the school of progressivism educational philosophy and collaboration with other schools of educational philosophy that are capable of supporting the achievement of a curriculum development orientation. The design of the Citizenship Education Curriculum based on the concept of Merdeka Belajar Kampus Merdeka in Higher Education has four aspects, namely planning, learning process, assessment, and evaluation.